Testing fiscal burden role on energy transition and economic recovery in South Asian economies - Guo, Li-fang (Frontiers in Environmental Science, 2022)
The aim of the study is to test the role of fiscal burden on energy transition and economic recovery. The major emphasis of this study, from this viewpoint, is on the repercussions of fiscal burden on energy transition through net GDP rate in eight different nations including the south Asia region, and to unlock the opportunities for economic recovery. In order to determine whether or not there were any effects of foreign fiscal burden on energy transition through net GDP rate in the data, the World Bank collected data for the period 2000–2018. The study conducted a GMM and quantile regression analysis to see if there were any effects of foreign fiscal burden on energy transition, and how it infers economic recovery. In spite of the facts that international fiscal burden has a considerable negative influence on economic recovery and energy transition. The robustness analysis validates these results, with influencing variables accounting for 39 percent and 31 percent, respectively, with the total external fiscal burden and external fiscal burden service of the total external fiscal burden. The findings of this research will be useful to government authorities in their attempts to design more efficient and effective economic strategies in the foreseeable future. Hence, study suggested the practical implications to reduce fiscal burden and accelerate economic recovery through energy transition.